The phytotelm tadpoles of Microhyla arboricola (Anura: Microhylidae) from Vietnam, with comments on reproductive biology and development - Vassilieva, Anna B.; Trounov, Vitaly L.; Poyarkov, Nikolay A., Jr.; Galoyan, Eduard A. (Zootaxa, 2017)
The reproductive biology of Microhyla arboricola (Microhylidae) was studied in two regions of the southern Annamite Mountains in Vietnam. M. arboricola is an obligate phytotelm-breeder that reproduces in water-filled tree hollows in montane evergreen forests. Clutches are attached above the water level in the hollows and contain 5–37 pigmented, relatively large eggs. Larvae hatch at markedly advanced stages and develop in water until metamorphosis is completed. The developing tadpoles are obligately oophagous and feed on conspecific eggs and embryos. M. arboricola tadpoles differ from tadpoles of pond-dwelling Microhyla species in their external morphology (extremely long tails, dorsolateral position of the eyes, dark pigmentation), digestive tract morphology (large, extensible larval stomach and short intestine), and oral morphology. The larval chondrocranium and hyobranchiumof M. arboricola is described. M. arboricola shares its habitat with other hollow-breeding species of anurans. To date, M. arboricola is the only known arboreal species of the genus Microhyla that has a unique reproductive mode. The ecological niche of this species differs greatly from those occupied by other microhylids of Indochinese Peninsula.